2017
DOI: 10.4314/ecajs.v21i3.11
|View full text |Cite
|
Sign up to set email alerts
|

The Jejunal Serosal Patch Procedure: A Successful Technique for Managing Difficult Peptic Ulcer Perforation

Abstract: Primary hyperparathyroidism is an endocrine disorder characterized by excessive and inappropriate release of Parathormone (PTH) from parathyroid glands resulting in diverse clinical manifestations involving the skeletal system in the form of bone and joint pains and pathological fractures, the gastrointestinal system in the form of dyspepsia from Peptic ulcer disease and pancreatitis, nephrolithiasis and other neuropsychiatric and nonspecific symptoms. There is nothing known about the epidemiology of this cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 1 publication
0
3
1
Order By: Relevance
“…This is consistent with several other studies done locally and in Africa which found a variable male predominance, 7.2, 6.6, 1.3 and 9 times in Black Lion Hospital (BLH), Zewditu Memorial Hospital (ZMH), Tanzanian and Nigerian studies respectively (5,6,7,8). However this is contrary to the common depiction in western series as a disease of the elderly female (9).…”
Section: Discussioncontrasting
confidence: 70%
“…This is consistent with several other studies done locally and in Africa which found a variable male predominance, 7.2, 6.6, 1.3 and 9 times in Black Lion Hospital (BLH), Zewditu Memorial Hospital (ZMH), Tanzanian and Nigerian studies respectively (5,6,7,8). However this is contrary to the common depiction in western series as a disease of the elderly female (9).…”
Section: Discussioncontrasting
confidence: 70%
“…10 Jejunal serosal patch is commonly used in the treatment of duodenal ulcer perforation, where it has eliminated the need for synthetic material and aids by providing a layer of protection. 6 Research supports the use of pyloric exclusion and jejunal serosal patch in select complex cases with a reduction in morbidity noted, but queries the benefit of its use in simpler cases because it may prolong hospital stay and confer no survival or outcome benefit. 11 – 13 There are multiple ways to establish nutrition following duodenal trauma and pyloric exclusion.…”
Section: Discussionmentioning
confidence: 97%
“…For more complex injuries, especially after blunt trauma where the injury has a tendency to evolve over a number of days with delayed leakage of repair (grade III–V), management remains divided. 3 5 One technique described is the jejunal serosal patch, which reinforces the primary repair by offering an additional layer of protection 6 to mitigate against leakage. Pyloric exclusion is another technique described after severe duodenal injury, as a temporary measure to prevent fluids entering the lumen of the duodenum from the stomach, thereby enabling primary repair without resection and, in theory, reducing leakage from the primary repair.…”
Section: Introductionmentioning
confidence: 99%
“…A review of current literature suggests a myriad of surgical techniques but no perfect solution. Some suggested techniques include omental patch with pyloric exclusion, controlled tube duodenostomy, jejunal pedicled graft or serosal patch, gastric disconnection and partial gastrectomy [25][26][27][28][29][30][31]. Many of the techniques are complex and require a high degree of surgical expertise, which may not be available in the emergency setting.…”
Section: Conclusion -Discussion and Review Of Literaturementioning
confidence: 99%